The Correlation between Student’s Interest and Their English Learning Outcomes: A Correlational Study at SMAN 5 Mataram - Alpina; Arafiq; Aziz, Atri Dewi (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to determine the correlation between students' interest and their English learning outcomes among grade XI students at SMAN 5 Mataram, as well as to identify the factors influencing students' interest in learning English. The significance of English language competency in a global society highlights the need to understand the variables affecting students' interest in learning. Using a mixed-method approach, this study combines qualitative data from interviews with quantitative data from questionnaires and documentation of students' English grades. A total of 36 students from grade XI–7 were selected as the sample through simple random sampling. The results indicated that the majority of students (63.89%) had a moderate interest in studying English; however, 61.11% did not meet the minimum competency criteria in English language learning. The Pearson correlation analysis revealed a positive and significant correlation (r = 0.511, p = 0.001 < 0.05) between students' interest and their English learning outcomes. Factors such as student experience, motivation, teaching methods, the learning environment, and the social environment were identified as influences on students' interest in learning. This study concludes that increasing student interest can significantly enhance their English learning outcomes.